Nonspecific Pyoinflammatory Lesions of the Spine: Spondylodiscitis, Epiduritis - A. V. Yarikov; A. P. Fraerman; O. A. Perlmutter; A. A. Denisov; S. V. Masevnin; I. I. Smirnov; A. N. Lavrenyuk (Неотложная медицинская помощь, 2019)
Nonspecific infectious lesions of the spine are relatively rare, difficult to diagnose and severe diseases of the spine. The urgency of treating nonspecific infectious spinal diseases is explained by an increase in the frequency of these diseases, new antibiotic-resistant strains of microorganisms, and the severity of the course and unsatisfactory treatment outcomes. In this review, we describe spondylodiscitis and epiduritis in detail. On the basis of literature data, we thoroughly studied and described etiology, clinical pattern and diagnosis of these diseases. We thoroughly covered modern laboratory and radiologic methods for the diagnosis of spondylodiscitis and epiduritis, such as spondylography, computed tomography, magnetic resonance imaging, scintigraphy, positron emission tomography of the spine and biopsy and described modern methods of conservative and surgical treatment. The particular attention is paid to the technique of surgical treatment of spondylodiscitis and epiduritis.